The use of resected SMAS as autologous graft for the correction of nasolabial folds during rejuvenating procedures: SMAS autologous graft for nasolabial folds corrections: a renewed “old-school” technique - Innocenti, Alessandro; Melita, Dario; Innocenti, Marco (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Despite several techniques are proposed, treatment of nasolabial folds is often challenging. During rejuvenation procedures, the SMAS could be redraped or partially resected during the procedure. The aim of this study is to investigate the use of obtained SMAS strip as autologous graft, because of its solid but pliable consistence and fatty composition, to correct nasolabial folds during procedures with SMAS resection.Methods Between 2015 and 2018, 23 patients underwent SMAS graft for nasolabial fold correction. All procedures were performed under local anesthesia and no other cosmetic treatments, including HA fillers, have been done in the past 12 months.Results: 22 patients were declared eligible for the study. 20 patients were female, accounting for 90,91%. Mean age was 53 years old. Ancillary procedures were performed in 17 patients, including upper blepharoplasty (3, 13,63%), upper and lower blepharoplasty (5, 22,73%) and submental neck lift with platysma plication (15, 68,18%). Mean follow-up was 9 months. No major complications have been recorded: only 1 case of minimal hematoma in the retroauricular region have been recorded and 1 patient required laser treatment for pathological scars. At follow-up, graft is completely integrated into the mid-fat compartment. As evinced from the FACE-Q analysis, the overall satisfaction rate is extremely high. These are very convincing data regarding the effectiveness of the technique and, despite a little bit longer downtime, is not invasive and led to natural long-lasting results event during motion.Conclusions: The use of SMAS graft during face-lift as nasolabial fold filler results in a satisfactory but natural filling of the folds, reducing the need for lateral tension and therefore assuring more natural results. Since its nature, SMAS, reduced in width to properly fit into the nasolabial fold, can be considered as an optimal autologous graft for replenish loss volumes of the face with aging.